Smartphone Purchasing Decisions Among Teenagers in Terms of Lifestyle, Brand Image and WOM Communication - Prabowo, Heri; Octaviani, Isna Catur; Dharmaputra, M Fadjar (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: The research was conducted because there are empirical phenomena as well as previous research phenomena, the empirical phenomenon of smartphone use among teenagers with use limited to ordinary activities, not to support productivity.Purpose: This research aims to analyze and discuss the influence of lifestyle and brand image on purchasing decisions, both directly and through word-of-mouth communication. Apart from that, to measure the influence of word-of-mouth communication on purchasing decisions.Design/methodology/approach: The method used is quantitative, which aims to analyze the relationship between variables and determine the influence of a variable on other aspects. The research methodology used in this research is the use of a survey, where the researcher provides a questionnaire as a data collection tool.Findings/Results: Brand image has no influence on purchasing decisions. Brand image influences word-of-mouth communication. Word-of-mouth communication influences purchasing decisions. Lifestyle influences purchasing decisions. Lifestyle influences word-of-mouth communication. And brand image influences purchasing decisions that are mediated by word-of-mouth communication. Lifestyle influences purchasing decisions, which are mediated by word-of-mouth communication.Conclusion: Lifestyle and word-of-mouth communication influence purchasing decisions. Brand image has no effect on purchasing decisions. The influence of brand image on purchasing decisions when mediated by word-of-mouth communication.Originality/value (state of the art): This study is a previous research that yielded different results. The findings indicate that brand image does not have a direct effect on purchasing decisions. However, when word-of-mouth communication is used as an intervening variable, both lifestyle and brand image influence purchasing decisions. Keywords: brand image, lifestyle, purchasing decisions, word of mouth communication